Economic Management Challenges and Opportunities for Traditional Market Clothing Traders - Nuzuliati Nuzuliati; Awaludin (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The era of digitalization has brought significant changes in various sectors of the economy, including traditional markets that are an important part of the local economy. This research aims to analyze the challenges and opportunities of economic management faced by clothing traders in traditional markets in the face of the digital era. Drawing on secondary data analysis from market reports, media articles, and academic studies, the study identified major barriers to merchant competitiveness, including e-commerce competition, low digital literacy, shifting consumer preferences towards online shopping, unstable local supply chains, and inadequate market infrastructure. The results of the study show that the main challenges faced by merchants include low digital literacy, fierce competition with e-commerce platforms, and limited capital to adapt to technology. This research provides strategic recommendations for traders to increase competitiveness, such as digital literacy training, social media optimization for marketing, and the development of partnerships with digital economy players.